The Use Of Teaching Media In Expression Orale (Speaking) Class At French Education Study Program - Sekeh, W E (Universitas Negeri Manado, 2019)
The purpose of this study is to find and describe the use of teaching media and find out its role in improving students’ learning outcomes at French Language Education Study Program of Manado State University. This research uses classroom action research methods. The results show that the use of teaching media effectively improved student learning outcomes by increasing stundents’ mastery of learning subject by 20% and increasing student learning outcomes by 11.34%. The use of teaching media makes the teaching and learning process more interesting and arouses student interest and motivation. Keywords: teaching media, CAR, learning outcomes, interests, motivation.